Implementation of energy justice into the energy transition - Vitošević Jovana; Đurđević Dragan (Megatrend Revija, 2022)
The initial definition of the theoretical concept of energy justice did not assume that it would be evaluated over time and become a conceptual framework that is applicable and can be materialized in practice. In fact, energy justice is today an instrument used to protect human rights in all elements of the energy sector and the energy transition. Although we talk about the energy transition in a positive connotation, a path towards something better and a change for the better, it can also have negative consequences. That continuous weighing between benefits and risks and the question of whether renewable energy will be available to everyone and at what price, and how it will affect consumers, gives the transition a much broader context in which it also has a great responsibility, and that belongs to the domain of energy justice. Also, the role of energy justice in the heterogeneous and layered relationship of migration and climate change is emphasized, because the consequences of the development of the energy system in the construction of production and consumption patterns were oft en unjust, and on the other hand, population displacement has the ability to seriously disrupt the economic prosperity and security of people. Therefore, the research of the multiple implications of energy justice in the process of energy transition and its outcomes can contribute to its fairness and the initiation of responsibility and protection.